2021
DOI: 10.3389/fendo.2021.706914
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Co-Transporter-2 Inhibitors in Non-Diabetic Adults With Overweight or Obesity: A Systematic Review and Meta-Analysis

Abstract: BackgroundSodium-glucose-cotransporter-2 (SGLT2) inhibitors have proven to be effective in improving glycemic control and lowering body weight in patients with type 2 diabetes mellitus. However, the efficacy and safety on weight loss in adults with overweight or obesity but not diabetes remain unclear. In this article, we aimed to identify the efficacy and safety of SGLT2 inhibitors in adults with overweight or obesity but not diabetes in randomized controlled studies (RCTs).MethodsWe searched for RCTs concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 35 publications
(68 reference statements)
1
16
0
Order By: Relevance
“…It has been shown that SGLT2 inhibitors can act directly on inflammatory pathways independent of hypoglycemic pathways ( 111 ). SGLT2 inhibitors are safe and well tolerated in adults who are overweight and obese but do not have diabetes ( 122 ). Under normal glucose conditions, SGLT2i inhibits SMC migration and proliferation by targeting il-17a-mediated oxidative stress, NLRP3 expression and inflammatory responses without inducing cell death ( 123 ).…”
Section: The Role Of An Sglt2 Inhibitor On the Nlrp3 Inflammasome: Po...mentioning
confidence: 99%
“…It has been shown that SGLT2 inhibitors can act directly on inflammatory pathways independent of hypoglycemic pathways ( 111 ). SGLT2 inhibitors are safe and well tolerated in adults who are overweight and obese but do not have diabetes ( 122 ). Under normal glucose conditions, SGLT2i inhibits SMC migration and proliferation by targeting il-17a-mediated oxidative stress, NLRP3 expression and inflammatory responses without inducing cell death ( 123 ).…”
Section: The Role Of An Sglt2 Inhibitor On the Nlrp3 Inflammasome: Po...mentioning
confidence: 99%
“…pressure. 1,2 Beneficial effects have also been reported in renal and cardiovascular disease, [3][4][5][6][7][8] and human use has increased considerably both in diabetic and non-diabetic patients in response to a growing body of evidence of clinical benefit. 9 Canagliflozin was the first SGLT2i registered for use in people in 2013 and was followed by others including dapagliflozin, empagliflozin and most recently, ertugliflozin.…”
mentioning
confidence: 99%
“…Sodium–glucose cotransporter 2 inhibitors (SGLT2i) were initially developed as a new class of human antidiabetic medications that lower insulin concentrations, promote weight loss and reduce blood pressure 1,2 . Beneficial effects have also been reported in renal and cardiovascular disease, 3–8 and human use has increased considerably both in diabetic and non‐diabetic patients in response to a growing body of evidence of clinical benefit 9 . Canagliflozin was the first SGLT2i registered for use in people in 2013 and was followed by others including dapagliflozin, empagliflozin and most recently, ertugliflozin 10 .…”
mentioning
confidence: 99%
“…The weight-reduction benefits of SGLT2 inhibitors as the mainstay of prediabetes management have been reported in multiple RCTs. A systematic review and meta-analysis of 6 RCTs with 872 adults with overweight or obesity without diabetes demonstrated that SGLT2 inhibitors significantly reduced absolute changes in body weight (−1.42 kg; 95% CI, −1.70 to −1.14 kg) and body mass index (−0.47; 95% CI, −0.63 to −0.31). Based on available evidence, SGLT2 inhibitors may be considered in treatment of prediabetes.…”
mentioning
confidence: 99%